Expression of p53, p21 and cyclin D1 in penile cancer: p53 predicts poor prognosis. Issue 3 (1st December 2011) - Gunia, Sven; Kakies, Christoph; Erbersdobler, Andreas; Hakenberg, Oliver W; Koch, Stefan; May, Matthias
Abstract : Aims: To evaluate the role of p53, p21 and cyclin D1 expression in patients with penile cancer (PC). Methods: Paraffin-embedded tissues from PC specimens from six pathology departments were subjected to a central histopathological review performed by one pathologist. The tissue microarray technique was used for immunostaining which was evaluated by two independent pathologists and correlated with cancer-specific survival (CSS). κ-statistics were used to assess interobserver variability. Uni- and multivariable Cox proportional hazards analysis was applied to assess the independent effects of several prognostic factors on CSS over a median of 32 months (IQR 6–66 months). Results: Specimens and clinical data from 110 men treated surgically for primary PC were collected. p53 staining was positive in 30 and negative in 62 specimens. κ-statistics showed substantial interobserver reproducibility of p53 staining evaluation (κ=0.73; p<0.001). The 5-year CSS rate for the entire study cohort was 74%. Five-year CSS was 84% in p53-negative and 51% in p53-positive PC patients (p=0.003). Multivariable analysis showed p53 (HR=3.20; p=0.041) and pT-stage (HR=4.29; p<0.001) as independent significant prognostic factors for CSS. Cyclin D1 and p21 expression were not correlated with survival. However, incorporating p21 into a multivariable Cox model did contribute to improved model quality for predicting CSS. Conclusions: In patients with PC, the expression of p53 in the primary tumour specimen can be reproducibly assessed and is negatively associated with cancer specific survival.